Duties And Authority Of PKPU Management Basen On Law No. 37 Of 2004 Concerning Bankruptcy And Suspension Debt Payment Obligations - Zeffrianto Sihotang (Journal of Law Science, 2021)
Suspension of Debt Payment Obligations (PKPU) is a way that can be done so that debtors avoid the bankruptcy process. In the PKPU process, one or more independent PKPU administrators are appointed to together with the PKPU debtor manage the assets of the PKPU debtor. The problem in this paper is about how the appointment of the management in PKPU, the relationship between the management and PKPU debtors, as well as the duties and authorities of the PKPU management as regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The research method used is a normative legal research method with a descriptive research nature and uses a juridical legal approach. Data collection was carried out by means of data collection in the form of library research in the form of books, articles, magazines and the internet which are closely related to the aims and objectives of writing this thesis. The data used is secondary data, namely primary legal materials, secondary legal materials and tertiary legal materials. The method used in analyzing the data is qualitative analysis. The conclusion of this paper is that the PKPU management is appointed by the Panel of Judges of the Commercial Court who examines and decides on the PKPU case with a decision. In PKPU, the relationship between management and debtors is very close based on the duties and authorities they have, so that in order to achieve the goals of PKPU, the management and debtors must always pay attention to and maintain good relations. Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations has regulated the duties and authorities of the PKPU management in managing the assets of PKPU debtors together with PKPU debtors treasure.